ICT aided steps in the learning of segmental phonetics - Martino, Daniela Lorena (2017)
The different perspectives that aim at explaining how pronunciation in a foreign language is acquired are key to developing activities that foster effective learning. In an attempt to explain the struggles faced by students when it comes to pronunciation in a foreign language, special attention has been given to the first language and the way it might interfere with the acquisition of L2/FL sounds. Polivanov (1931, 1964) and Trubetzkoy (1939, 1969) focused on the effect of speech perception on phonology arguing that sounds in a second language are perceived through the phonological system of the first language and failing to articulate a certain sound was the result of perceiving it erroneously. In this way the authors pointed out that inexact L2 production is the result of erroneous perception, suggesting that L1 operates as a phonological filter through which the L2 sounds are processed. In the same line, Dupoux (2002, p. 172) described the “phonological deafness” that learners suffer from as they strive to discriminate sounds in a foreign language using a “processing apparatus specifically tuned to their maternal language” bringing about a lot of difficulty “in dealing with sound structures that are alien to the language they heard as infants”. Flege (2003) proposes the speech learning model (SLM) which posits that the L1 and L2 phonetic subsystems influence each other as a result of coexisting in a common phonological space leading to L1 and L2 sounds either merging into category assimilation or shifting away from each other (category dissimilation). The need to lay particular emphasis on learners’ perception becomes evident from the previously mentioned theories. It is interesting to note that L2 learners might be able to discriminate the acoustic difference between phones used to realize two categories on an auditory basis but may fail to do so phonetically. Therefore, perceptual awareness of categorical distinctions would seem to take place before the ability to implement such distinctions, with time and practice as key to establishing “the motor control patterns needed for producing new phones in an L2” (Flege, 1987, p. 290). This explains the practice stage that should follow the work on perception. In connection to the motor control referred above, the concept of proprioception –internal kinesthetic awareness of the position and movement of our muscles and parts of the body– takes on paramount importance. Listen and repeat exercises on their own fail to help students develop “proprioceptive or kinesthetic intelligence that can gradually liberate the learner from the oral and aural grip of their mother tongue pronunciation habits” (Underhill, 2012). Pronunciation, being a physical and muscular activity –a motor skill–, should not be taught on a purely cognitive basis. The research done on the acquisition of L2/EF pronunciation serves as framework for the design of a set of stages and activities that can help learners advance from controlled to automatic processing (Celce-Murcia, Brinton & Goodwin, 2006). The advance of technology provides learners with an array of tools that can not only aid but also accompany learners in such process.